ANALISIS DAMPAK PENGGUNAAN BAHASA DAERAH TERHADAP KESULITAN BELAJAR BAHASA INDONESIA SISWA - Wulandari; Hijrah Purnaman Sari Ariga; Muhammad Darwis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the dominant use of local languages in students' daily lives, which is suspected to affect their Indonesian language learning. The research is important because Indonesian serves as the language of instruction in education and plays a significant role in supporting students' academic success. The purpose of this study was to analyze the impact of local language use on students' difficulties in learning Indonesian at SMP Negeri 31 Takengon. This study employed a descriptive qualitative approach using observation, interviews, documentation, and tests as data collection techniques. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that local languages remain dominant in family and community environments. Their impact can be seen in limited vocabulary mastery, difficulties in reading comprehension, difficulties in distinguishing synonyms and antonyms, as well as the occurrence of code-mixing and language interference. In addition, low reading interest and environmental factors also influence students' language abilities. Therefore, the habituation of proper Indonesian language use and the strengthening of literacy culture are needed to improve students' language proficiency.